2018
DOI: 10.1177/1362361318793408
|View full text |Cite
|
Sign up to set email alerts
|

Object personification in autism: This paper will be very sad if you don’t read it

Abstract: Object personification is the attribution of human characteristics to non-human agents. In online forums, autistic individuals commonly report experiencing this phenomenon. Given that approximately half of all autistic individuals experience difficulties identifying their own emotions, the suggestion that object personification may be a feature of autism seems almost paradoxical. Why would a person experience sympathy for objects, when they struggle to understand and verbalise the emotions of other people as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 18 publications
6
48
2
Order By: Relevance
“…The findings build on results from a recent study that found a high proportion of autistic individuals anthropomorphize inanimate objects. 2 Those who spoke to us had mixed views regarding whether the phenomenon was positive, neutral, or negative. Participants in both groups explained that they not only derived comfort from their personal relationship with nonhuman agents but also worried about their well-being-which for some, could lead to great distress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings build on results from a recent study that found a high proportion of autistic individuals anthropomorphize inanimate objects. 2 Those who spoke to us had mixed views regarding whether the phenomenon was positive, neutral, or negative. Participants in both groups explained that they not only derived comfort from their personal relationship with nonhuman agents but also worried about their well-being-which for some, could lead to great distress.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of 87 autistic and 263 nonautistic adults in the United Kingdom revealed that anthropomorphism was reported more commonly among autistic individuals, and perhaps more often (and continuing later in life) than in the general population. 2 Furthermore, various descriptions from autistic individuals on internet blogs and forums, as well as some autobiographical accounts, seem to elaborately describe the perceived mental states of nonhuman agents and include detailed expressions of empathy toward the agents. [3][4][5][6] (Note: since anthropomorphism leads to perceiving nonhuman entities as having agency, anthropomorphized entities are referred to as ''agents'' within the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, there may be a critical difference between perceiving animated objects in mentalistic terms and explicitly ascribing them mental states. A recent study found that roughly half of adults with autism spontaneously personify objects ( White and Remington, 2018 ). This finding may call into question the logic of our argument that social cognition and anthropomorphism are related.…”
Section: Discussionmentioning
confidence: 99%
“…Tahiroglu (2012) found evidence in 4- to 6-year-olds of a relation between false belief understanding (false contents task) and anthropomorphism (using an interview-style measure), but this relation was not significant using other theory of mind measures and a narrative measure of anthropomorphism of animated shapes (akin to the procedure used by Castelli et al, 2000 ). Recent work suggests that adults with autism personify objects at higher rates than non-autistic adults ( White and Remington, 2018 ) – a result that is striking given the typical deficits in theory of mind among individuals with autism (see also Atherton and Cross, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Autistic perception has been described as providing a body-world experience that does not lend itself easily to the creation of social meanings (Manning 2016) and autistic people often depict their sensory experience of objects in powerful terms. The experience of objects is sometimes described as giving rise to a greater sense of connectedness than with human beings and to a feeling that objects are alive and communicable with (White & Remington 2019, Williams 1998. In autistic autobiographies, writers regularly describe themselves as children attending to the material features of their environment more than any social aspects, finding these to be less overwhelming, more meaningful and a source of greater satisfaction in terms of relatedness (Sainsbury 2009).…”
Section: Introductionmentioning
confidence: 99%